Biomimetic electrospun nanofibrous scaffold for tissue engineering: preparation, optimization by design of experiments (DOE), in-vitro and in-vivo characterization - Anjum, Shabnam; Li, Ting; Arya, Dilip Kumar; Ali, Daoud; Alarifi, Saud; Yulin, Wang; Hengtong, Zhang; Rajinikanth, P. S.; Ao, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
Electrospinning is a versatile method for fabrication of précised nanofibrous materials for various biomedical application including tissue engineering and drug delivery. This research is aimed to fabricate the PVP/PVA nanofiber scaffold by novel electrospinning technique and to investigate the impact of process parameters (flow rate, voltage and distance) and polymer concentration/solvent combinations influence on properties of electrospun nanofibers. The in-vitro and in-vivo degradation studies were performed to evaluate the potential of electrospun PVP/PVA as a tissue engineering scaffold. The solvents used for electrospinning of PVP/PVA nanofibers were ethanol and 90% acetic acid, optimized with central composite design (CCD) via Design Expert software. NF-2 and NF-35 were selected as optimised nanofiber formulation in acetic acid and ethanol, respectively and their characterization showed diameter of 150-400 nm, tensile strength of 18.3 and 13.1 MPa, respectively. XRD data revealed the amorphous nature, and exhibited hydrophilicity (contact angles: 67.89° and 58.31° for NF-2 and NF-35). Swelling and biodegradability studies displayed extended water retention as well as delayed in-vitro degradation. FTIR analysis confirmed solventindependent interactions. Additionally, hemolysis and in-vitro cytotoxicity studies revealed the nontoxic nature of fabricated scaffolds on RBCs and L929 fibroblast cells. Subcutaneous rat implantation assessed tissue response, month-long biodegradation, and biocompatibility through histological analysis of surrounding tissue. Due to its excellent biocompatibility, this porous PVP/PVA nanofiber has great potential for biomedical applications.